The Effect of Organizational Justice on Job Satisfaction among Secondary School Teachers - Ali Zgair Ghran, Laith; S. Jameel, Alaa; Rahman Ahmad, Abd (International Journal of Psychosocial Rehabilitation, 2020)
Job satisfaction and organizational justice one of the topics which neglected in the context of Middle East countries in general and particularly in Iraq. The study aims to find the effect of organizational justice on job satisfaction among secondary schools teachers and enrich the body of knowledge in Iraq and the Middle East countries. The study conducted in 8 secondary schools in Heet city province of Anbar, Iraq, 98 valid questionnaires were analysed by SPSS. The results showed the components of organizational justice’s distributive justice and interactional justice are positively effect on job satisfaction. However, distributive justice found a high effect on Job satisfaction. While, Procedural justice found non-significant effect on job satisfaction may because of the environment and policy of public schools in Iraq which is directly related to government policy in case of, promotions, salary and employment etc. This result helps schools administration to manage the schools and understand teachers desire better than before. Meanwhile, teachers, when feel treated fairly from school administration and the rewards are distributed fairly and equitable in the school will lead to increase job satisfaction and could increase their productivity and performance.